(untitled) (Eurasian Medical Research Periodical, 2023)
Despite the introduction of modern diagnostic methods, tactics and treatment, the risk of developing early postoperative complications remains high. One of the most difficult moments in practical surgery is making a decision about the need for repeated surgery if complications develop in the early postoperative period. According to the literature, the frequency of relaptomies паротомийvaries from 0.5 to 8% of the total. h1a ofsurgical interventions performed on the abdominal organs, with a mortality rate of up to 70% [1, 2, 3, 4]. Difficulties in diagnosing complications in the early postoperative period are caused by a smaller expression of the clinical picture, erasure. withimptoma on the background of intensive care. Relaparotomy is a repeated section of the abdominal cavity, which is performed with the introduction of complications.